2013
DOI: 10.1021/es303989u
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Transfer of Contaminants and Reduced Reproductive Success of Southern Toads (Bufo [Anaxyrus] terrestris) Exposed to Coal Combustion Waste

Abstract: Bioaccumulation of contaminants and subsequent maternal transfer to offspring are important factors that affect the reproductive success of wildlife. However, maternal transfer of contaminants has rarely been investigated in amphibians. We examined maternal transfer of trace elements in southern toads ( Bufo[Anaxyrus] terrestris) residing in two locations: (1) an active coal combustion waste (CCW) disposal basin and adjacent 40-ha floodplain contaminated with CCW over 35 years ago and (2) an uncontaminated ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 59 publications
1
33
0
Order By: Relevance
“…, , Metts et al. ). Because of their ubiquity and occurrence in contaminated habitats, these species represent excellent models for investigation into long‐term population‐level effects of Cu contamination.…”
Section: Methodsmentioning
confidence: 99%
“…, , Metts et al. ). Because of their ubiquity and occurrence in contaminated habitats, these species represent excellent models for investigation into long‐term population‐level effects of Cu contamination.…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately we cannot attribute our observed effects to differential contamination history between wetlands because we had no replication of the two wetland types (reference vs. contaminated). However, previous amphibian studies conducted on populations from D-Area wetlands have documented 1) elevated body burdens of a suite of metals in adults, and 2) maternal transfer of metals to embryos, which correlated with reduced embryonic and larval viability (Hopkins et al 2006, Metts et al 2013). Although we did not measure maternal transfer, our data are consistent with other studies that have found negative effects of maternal transfer of heavy metals on offspring size and increased time to complete metamorphosis ).…”
Section: Factormentioning
confidence: 99%
“…Among elements associated with coal fly ash, Hg and Se are of particular concern because they are known to cause negative reproductive effects in oviparous wildlife (e.g., Coyle et al, 1993;Skorupa, 1998;Janz et al, 2010;B.C. Hopkins et al, 2013a;Metts et al, 2013). Our results suggest that the 2008 coal fly-ash spill affected concentrations of these elements in turtle tissues (Table 1), but accumulation resulted in concentrations below those needed to elicit adverse effects at the time we conducted our study multiple years after remediation.…”
Section: Discussionmentioning
confidence: 80%